2014
DOI: 10.3109/19396368.2014.933984
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine induces changes in the testicle and testosterone in adult male rats exposed via placenta and lactation

Abstract: Fluoxetine is a selective serotonin reuptake inhibitor used to treat depression in pregnant and nursing women. However, recent studies have shown adverse effects in the male reproductive system after fluoxetine treatment. Aiming to analyze the extent of damage caused by fluoxetine in the testicle and safe doses for treatment during the perinatal period, the present study analyzed the effects of in utero exposure and exposure during lactation to fluoxetine in spermatogenesis of male rat offspring in adulthood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
0
5
0
2
Order By: Relevance
“…On the other hand, rat testicular weight was decreased after high dose serotonin administration over 4 days (Hedger et al ., ). In addition, a reduction in testicular weight has been reported in adult male rats exposed to an SSRI in early life via the placenta and during lactation (de Oliveira et al ., ; Monteiro Filho et al ., ). These could indicate that testicular weight is affected when animals undergo long‐term stress stimulation, as well as when exposed to antidepressants.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, rat testicular weight was decreased after high dose serotonin administration over 4 days (Hedger et al ., ). In addition, a reduction in testicular weight has been reported in adult male rats exposed to an SSRI in early life via the placenta and during lactation (de Oliveira et al ., ; Monteiro Filho et al ., ). These could indicate that testicular weight is affected when animals undergo long‐term stress stimulation, as well as when exposed to antidepressants.…”
Section: Discussionmentioning
confidence: 97%
“…Supporting this notion, previous studies suggested that SSRIs reduce male fertility by affecting semen quality (reviewed by Norr et al , 2016 ; Sylvester et al , 2019 ; Beeder and Samplaski, 2020 ). Treatment of rodents with SSRIs reduced the sperm count, sperm motility, testicular weight, length of seminiferous tubules, and, thereby, male fertility ( Bataineh and Daradka, 2007 ; Attia, and Bakheet, 2013 ; Monteiro Filho et al , 2014 ; Galal et al , 2016 ; Lyons et al , 2016 ; Atli et al , 2017 ). In men, intake of SSRIs was associated with reduced sperm concentration, a higher number of morphologically abnormal sperm, and an increase in DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studied demonstrated that FLX can affect sexual brain differentiation, sexual behavior, testicular development and sperm production in rat offspring exposed in utero and/or through lactation [ 27 , 28 , 29 , 30 ]. Mueller et al showed that FLX can act as an estrogen receptor agonist both in vitro and in vivo [ 3 ].…”
Section: Discussionmentioning
confidence: 99%